2007
DOI: 10.1094/phyto-97-6-0702
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biological Characterization of Tomato chlorotic mottle virus Suggests that Recombination Underlies the Evolution and Diversity of Brazilian Tomato Begomoviruses

Abstract: Tomato chlorotic mottle virus (ToCMoV) is an emerging begomovirus species widely distributed throughout tomato-growing regions of Brazil. ToCMoV appears to have expanded its geographic range recently, invading tomato-growing areas that were free of begomovirus infection before 2004. We have determined the first complete genome sequence of an infectious ToCMoV genome (isolate BA-Se1), which is the first begomovirus species isolated in the northeast of Brazil. When introduced by particle bombardment into tomato,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 49 publications
6
42
0
4
Order By: Relevance
“…Both the hairpinloop structure and iteron have been found in all geminivirus sequenced to date and this might be used for analysis of their genetic diversity. It was known that differences in the common region may indicate a different begomovirus strain (Hidayat et al 1999;Chatchawankanphanich and Maxwell 2002;Sukamto et al 2005;Ribeiro et al 2006;Santoso et al 2008). It was found in our present research that three isolates of begomovirus infecting pepper in West Sumatra (PepPYK1-1, PepAg2-1 and PepAg2-4) have a hairpin loop those found in Java, which commonly caused bright yellow colouring (Sulandari 2004).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Both the hairpinloop structure and iteron have been found in all geminivirus sequenced to date and this might be used for analysis of their genetic diversity. It was known that differences in the common region may indicate a different begomovirus strain (Hidayat et al 1999;Chatchawankanphanich and Maxwell 2002;Sukamto et al 2005;Ribeiro et al 2006;Santoso et al 2008). It was found in our present research that three isolates of begomovirus infecting pepper in West Sumatra (PepPYK1-1, PepAg2-1 and PepAg2-4) have a hairpin loop those found in Java, which commonly caused bright yellow colouring (Sulandari 2004).…”
Section: Discussionsupporting
confidence: 52%
“…The type of symptoms associated with the disease in West Sumatra is different from The identity of begomovirus infecting pepper in West Sumatra was determined based on their hairpin-loop structure and repetitive sequence (iteron) found in the common region. These hairpin loop structure has been found in all geminivirus sequenced so far (Zhou et al 2003) and iteron is known as the specific-binding site of the geminivirus replicationassociated proteins (Ribeiro et al 2006). Both the hairpinloop structure and iteron have been found in all geminivirus sequenced to date and this might be used for analysis of their genetic diversity.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, the B biotype of B. tabaci colonizes a wide range of plants and is highly mobile, being able to fly over short distances or traveling up to several kilometers when assisted by the wind (Byrne, 1999). These characteristics facilitate the transmission of indigenous begomoviruses to new cultivated hosts, increasing the probability of novel, recombinant variants arising from mixed infections (Ribeiro et al, 2007). The current study investigated the species diversity of begomoviruses infecting malvaceous and compositae weeds in Brazil to assess the importance of these hosts as begomovirus reservoirs and as sources of novel viruses to crop plants.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that recombination plays an important role in the generation of genetic variability in begomoviruses in Brazil (Galvão et al, 2003;Inoue-Nagata et al, 2006;Ribeiro et al, 2007;Silva et al, 2011a,b) and worldwide (Pita et al, 2001;Monci et al, 2002;García-Andrés et al, 2006, 2007a. Recombination analysis showed the occurrence of inter-and intraspecific recombination events in the Rep, CP and CR of the viral isolates detected in Sida spp.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, recombination plays a significant role in the evolution of these viruses and this eventually results in the emergence of new disease phenotypes (Melgarejo, 2011;Kon and Gilbertson, 2012). Therefore, it is not surprising that recombinant begomoviruses have been reported in all tomato production areas of the world (Kirthi et al, 2002(Kirthi et al, , 2004Garcia-Andres et al, 2007;Lefeuvre et al, 2007b;Prasanna and Rai, 2007;Ribeiro et al, 2007;Kon and Gilbertson, 2012).…”
Section: Intraspecific and Interspecific Diversitymentioning
confidence: 99%